PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE THE LEARNING CELL DISERTAI HANDOUT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 17 PADANG - Adriani, Adriani; Zulfaneti, Zulfaneti; Suryani, Mulia (Pendidikan Matematika, 2014)
ABSTRACTThis research was carried out for the studentsâ low activities and ability in mathematics concept. The aim of the research was to reveal the studentsâ activities by using The Learning Cell active learning strategy and to see whether the mathematics conceptual understanding of the students taught by using The Learning Cell active learning strategy was better than that of students taught by using conventional learning in class VII I of SMPN 17 Padang. This was an experimental research. Based on the result data analysis it was found that, in general, the studentsâ activity improved in each meeting. The result of hypothesis test showed that the value of tcalculated (2,01) was higher than ttable (1,645) indicating that the hypothesis was accepted. This result signified that the mathematics conceptual understanding of the students taught by using The Learning Cell active learning strategy was better than that of students taught by using conventional learning in class VII I of SMPN 17 Padang registered in academic year 2013/2014.Â